2017
DOI: 10.1007/s11104-017-3352-4
|View full text |Cite
|
Sign up to set email alerts
|

An energy-dispersive X-ray fluorescence method for analysing Fe and Zn in common bean, maize and cowpea biofortification programs

Abstract: Background and aims Biofortification breeding programs have the need for rapid and accurate screening methods to identify nutrient dense genotypes. This study explores the use of energy dispersive x-ray fluorescence (EDXRF) for the rapid screening of iron (Fe) and zinc (Zn) concentration in three coarse-grain crops; common bean, maize and cowpea. Methods Bean, maize and cowpea seed was provided from biofortification breeding programs and analysed with Inductively Coupled Plasma -Mass Spectrometry (ICP-MS) to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 23 publications
2
34
0
1
Order By: Relevance
“…based on peak area calibration in table salt, while Guild et al (2017) showed the advantages of using a non-matrix-matched calibration in grain crops for calibrating XRF instruments.…”
Section: Reference Valuesmentioning
confidence: 99%
See 1 more Smart Citation
“…based on peak area calibration in table salt, while Guild et al (2017) showed the advantages of using a non-matrix-matched calibration in grain crops for calibrating XRF instruments.…”
Section: Reference Valuesmentioning
confidence: 99%
“…beans, rice, pearl millet, maize, cowpea and wheat (Guild et al, 2017). However, the potential of using XRF for analyzing mineral concentrations in potato tubers and other root and tuber crops…”
Section: Introductionmentioning
confidence: 99%
“…2016). Coupled with advances in technologies for assessing Zn, plant scientists can more rapidly measure Zn concentration in maize kernels using the energy dispersive x-ray fluorescence (XRF) assays (Guild et al . 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to VAD, iron deficiency anemia (IDA) commonly affects preschool age children and women [18,19]. Consequently, iron deficiency anemia is linked to maternal and perinatal mortality, and impairment of cognitive skills and physical activity [18][19][20][21]. Unfortunately, IDA is disproportionately prevalent in South Asia and Africa where 43% and 37%, respectively, of maternal mortality are attributed to IDA [19].…”
Section: Key Micronutrients Under Considerationmentioning
confidence: 99%
“…Zn is an essential micronutrient influencing gene expression, cell development and replication. A mortality rate of close to a million children annually is attributable to Zn deficiency because it is associated with the prevalence of diseases such as diarrhea, pneumonia, and malaria [21].…”
Section: Key Micronutrients Under Considerationmentioning
confidence: 99%